2015
DOI: 10.1021/acs.energyfuels.5b01174
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Bitumen from Oil Sands Using Deep Eutectic Ionic Liquid Analogues

Abstract: It is demonstrated that bitumen can be separated from "water-wet" Alberta oil sands and "oil-wet" Utah oil sands using a so-called analogue ionic liquid (IL) based on deep eutectic mixtures of choline chloride and urea (ChCl/U) together with a diluent such as naphtha. Unlike conventional ILs, these eutectics are relatively cheap and environmentally friendly. The process is straightforward and involves simply mixing the components at ambient temperatures followed by standard solid/liquid and liquid/liquid separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 31 publications
(50 reference statements)
3
51
0
Order By: Relevance
“…When 20% water was added, the viscosity of ChCl-MA ionic liquid decreased by 90%, followed by the decrease of ChCl/U by 85%, and the viscosity change of ChCl-EG decreased by 50% at least. This is consistent with previous results on ionic liquid viscosity [12]. Then, the viscosity of the aqueous solution of ionic liquids decreased with the decrease of the mass concentration of ionic liquid and it finally tended to be close to the viscosity of water (1 mPa s) as shown in Figure 1a.…”
Section: Ionic Liquids and Deep Eutectic Solvents Physicochemical Propertiessupporting
confidence: 92%
“…When 20% water was added, the viscosity of ChCl-MA ionic liquid decreased by 90%, followed by the decrease of ChCl/U by 85%, and the viscosity change of ChCl-EG decreased by 50% at least. This is consistent with previous results on ionic liquid viscosity [12]. Then, the viscosity of the aqueous solution of ionic liquids decreased with the decrease of the mass concentration of ionic liquid and it finally tended to be close to the viscosity of water (1 mPa s) as shown in Figure 1a.…”
Section: Ionic Liquids and Deep Eutectic Solvents Physicochemical Propertiessupporting
confidence: 92%
“…Recent work at lab and pilot scales has shown that bitumen can be cleanly and easily separated from “water-wet” and “oil-wet” oil sands, regardless the nature and grade of ore, using ionic liquid assisted solvent extraction (ILASE) at ambient temperature. This technology was initially developed by Painter and his co-workers at Pennsylvania State University. As illustrated in Figure , the process involves first the formation of a three-phase system obtained by simply mixing the ore with an ionic liquid (IL) and an organic solvent, followed by the standard solid–liquid and liquid–liquid separations. The phases in the extracted mixture are distinct: a layer of sand and clays on the bottom, an IL layer in the middle, and an organic layer of bitumen/solvent on the top, which could be readily removed by decantation or other means.…”
Section: Technological Methodsmentioning
confidence: 99%
“…In recent years, ionic liquids (ILs) have been intensively studied for extraction due to their unique physical and chemical properties such as nonflammability, very low volatility, high thermal and chemical stabilities, wide range of liquids, and flexible design strategy. , Considering all these features, ILs can potentially become alternative to replace volatile organic solvents in extraction processes, especially for mixtures which are difficult to separate (e.g., recovery of bitumen from oil or sands, , separation of benzene from cyclohexane, thiophenic sulfur compounds from hydrocarbons, , ethyl acetate from ethanol, and high value-added compounds from biomass ). For the recovery of vitamin E, ILs as extractant have also been reported.…”
Section: Introductionmentioning
confidence: 99%